2019
DOI: 10.3847/1538-4357/ab2be6
|View full text |Cite
|
Sign up to set email alerts
|

KSP-SN-2016kf: A Long-rising H-rich Type II Supernova with Unusually High 56Ni Mass Discovered in the KMTNet Supernova Program

Abstract: We present the discovery and the photometric and spectroscopic study of H-rich Type II supernova (SN) KSP-SN-2016kf (SN2017it) observed in the KMTNet Supernova Program in the outskirts of a small irregular galaxy at z 0.043 within a day from the explosion. Our high-cadence, multi-color (BV I ) light curves of the SN show that it has a very long rise time (t rise 20 days in V band), a moderately luminous peak (M V −17.6 mag), a notably luminous and flat plateau (M V −17.4 mag and decay slope s 0.53 mag per 100 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 108 publications
0
10
0
Order By: Relevance
“…If He-shell DDet is the origin of surface Fe-peak elements in SN 2018aoz, it would imply that detonations of He-shells as thin as ∼ 0.01 M can successfully initiate normal Type Ia SNe, consistent with the predictions of our simulations and other recent simulations 7,48 . In our best-fit He-shell DDet model for SN 2018aoz, 12.9% of the outer 1% of the ejecta by mass is composed of 56 Ni, 52 Fe, and 48 Cr. Although this is comparable to the amount of radioactive material needed to reproduce the infant-phase excess emission in SN 2018aoz (see section "Distribution of Fe-peak Elements in the Extreme Outer Ejecta"), the Heshell DDet model under-predicts the emission 0.5 days (Supplementary Section 7.1), indicating that either the current He-shell DDet models do not fully capture radioactive heating at early times or another source of emission is also required (e.g., ejecta collision with a companion 49 ).…”
Section: Nature Of Sn 2018aoz and Implications For Type Ia Sn Originsmentioning
confidence: 93%
See 1 more Smart Citation
“…If He-shell DDet is the origin of surface Fe-peak elements in SN 2018aoz, it would imply that detonations of He-shells as thin as ∼ 0.01 M can successfully initiate normal Type Ia SNe, consistent with the predictions of our simulations and other recent simulations 7,48 . In our best-fit He-shell DDet model for SN 2018aoz, 12.9% of the outer 1% of the ejecta by mass is composed of 56 Ni, 52 Fe, and 48 Cr. Although this is comparable to the amount of radioactive material needed to reproduce the infant-phase excess emission in SN 2018aoz (see section "Distribution of Fe-peak Elements in the Extreme Outer Ejecta"), the Heshell DDet model under-predicts the emission 0.5 days (Supplementary Section 7.1), indicating that either the current He-shell DDet models do not fully capture radioactive heating at early times or another source of emission is also required (e.g., ejecta collision with a companion 49 ).…”
Section: Nature Of Sn 2018aoz and Implications For Type Ia Sn Originsmentioning
confidence: 93%
“…Such a selective suppression of flux can only be from line absorption. Fe-peak and associated nucleosynthetic elements, including 56 Ni, 52 Fe, 48 Cr, 44 Ti, and their decay products, are the elements expected in Type Ia SNe that can significantly suppress flux in the vicinity of 5000 Å. While H and He lines can blanket 4000 Å41,42 , they are not generally expected in Type Ia SNe and most of the B-band flux would not be significantly affected.…”
Section: Origin Of the Infant-phase B-band Plateau And Red B − V Colormentioning
confidence: 96%
“…We are conducting a systematic study of dwarf galaxies in nearby galaxy groups using data from the KMTNet (Korea Microlensing Telescope Network) Supernova Program (KSP; Moon et al 2016). KSP is a program to search for supernovae and optical transients (He et al 2016;Antoniadis et al 2017;Brown et al 2018;Lee et al 2019;Afsariardchi et al 2019) using three 1.6-m telescopes located at the Cerro Tololo Inter-American Observatory (CTIO, Chile), the South African Astronomical Observatory (SAAO, South Africa), and the Siding Spring Observatory (SSO, Australia). When several hundred KSP images in each field are stacked, the program provides deep BV I images reaching a sensitivity of about 28 mag arcsec −2 within a 1.5 acrsec radius aperture.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, attributing the full tail luminosity to 56 Ni would lead to an overestimate of the true values. Within this context, it is notable that while simulations of neutrino-driven core-collapse SNe (Sukhbold et al 2016;Ertl et al 2019) are able to self-consistently produce the range of M Ni values observed in H-rich Type II SN (∼0.004-0.13 M ; Müller et al 2017, Afsariardchi et al 2019, they are unable to produce M Ni values as high as those derived for the upper ∼30% of our SESN sample (see Figures 7 and 8). It was for this reason that Ertl et al (2019) invoked magnetars to explain the observed light curves of SESNe.…”
Section: Consequences Of M Ni Discrepancy With Type Ii Snementioning
confidence: 74%